Competency Disparities and Human Resource Challenges in The Implementation of Social Welfare Service Standards - Rohyati, Eni; Rakhman, Arif Kurniar; Harahap, Dewi Handayani (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The implementation of Social Welfare Service Standards (SPM) is a very important policy tool to ensure that the basic rights of Social Welfare Service Recipients (PPKS) are fulfilled. However, in practice, the implementation of these standards still faces many problems, especially those related to human resources. The purpose of this study is to analyse the imbalance of competencies and challenges that exist in human resources when implementing Social Welfare Service Standards in the Special Region of Yogyakarta.The approach used in this study is qualitative with a descriptive evaluative method, which applies the Context, Input, Process, and Product (CIPP) evaluation model. Data were obtained through in-depth interviews, observations, and document analysis using purposive sampling techniques from key informants directly involved in the implementation of social welfare services. The results of this study indicate a significant difference between the competency standards set in the regulations and the actual capabilities of human resources in the field. Several contributing factors are the limited number of professionals, lack of specialisation, minimal continuing training, and an unbalanced distribution of workloads, resulting in high workloads and overlapping tasks. As a result, the services provided tend to be administrative and reactive in nature, which means that the social rehabilitation objectives in the areas of social function recovery and independence of service recipients have not been optimally achieved. Therefore, improving competencies through systematic training, regulating workloads based on needs analysis, and developing a professional human resource management system are important for improving the quality and effectiveness of social welfare services.